Using Reclaimed Water to Irrigate Turfgrass – Lessons Learned from Research with Phosphorus - George Hochmuth; Jinghua Fan; Jason Kruse; Jerry Sartain (EDIS)
Municipal wastes are treated at a wastewater treatment facility to produce biosolids and reclaimed water. Reclaimed water treated by filtration and chlorination is safe to use for designated purposes, such as residential landscape irrigation. Florida began using reclaimed water in 1966, and it is a leading state for using reclaimed water. Approximately 660 million gallons of reclaimed water are used every day in Florida, and the state encourages using reclaimed water as an alternative water source to reduce the pressure on potable water supplies. This 3-page fact sheet summarizes the results of a recent research project and provides research-based information for improving nutrient and water management with reclaimed water irrigation of turfgrass. Written by George Hochmuth, Jinghua Fan, Jason Kruse, and Jerry Sartain, and published by the UF Department of Soil and Water Science, November 2013. http://edis.ifas.ufl.edu/ss592